2020
DOI: 10.2337/dc20-0706
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Determinants of Aerobic Exercise Capacity in Adults With Type 2 Diabetes

Abstract: To assess the relationship between subclinical cardiac dysfunction and aerobic exercise capacity (peak VO 2) in adults with type 2 diabetes (T2D), a group at high risk of developing heart failure. RESEARCH DESIGN AND METHODS Cross-sectional study. We prospectively enrolled a multiethnic cohort of asymptomatic adults with T2D and no history, signs, or symptoms of cardiovascular disease. Age-, sex-, and ethnicity-matched control subjects were recruited for comparison. Participants underwent bioanthropometric pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 46 publications
3
23
1
Order By: Relevance
“…Our findings confirm most previous reports (although not all [ 39 ]) describing reduced S’ velocity of the mitral annulus measured through tissue Doppler in patients with T2D during exercise [ 40 42 ], an observation that was also related to myocardial fibrosis as measured though cardiac magnetic resonance [ 43 ]. Given the large prevalence of diastolic dysfunction in T2D subjects [ 38 ] and the results of a recent report by Gulsin et al [ 44 ], we were surprised not to see alteration in E/e’ in our population with effort intolerance, neither at rest nor during exercise. In the work of Gulsin and coll., however, diastolic indices were not measured during exercise, and the association was essentially driven by a minority of subjects with a baseline E/e’ > of 12.5, and in the whole population the effect size was small with + 1 units of E/e’ justifying -0.3 ml/kg/min of VO 2peak .…”
Section: Discussionmentioning
confidence: 52%
“…Our findings confirm most previous reports (although not all [ 39 ]) describing reduced S’ velocity of the mitral annulus measured through tissue Doppler in patients with T2D during exercise [ 40 42 ], an observation that was also related to myocardial fibrosis as measured though cardiac magnetic resonance [ 43 ]. Given the large prevalence of diastolic dysfunction in T2D subjects [ 38 ] and the results of a recent report by Gulsin et al [ 44 ], we were surprised not to see alteration in E/e’ in our population with effort intolerance, neither at rest nor during exercise. In the work of Gulsin and coll., however, diastolic indices were not measured during exercise, and the association was essentially driven by a minority of subjects with a baseline E/e’ > of 12.5, and in the whole population the effect size was small with + 1 units of E/e’ justifying -0.3 ml/kg/min of VO 2peak .…”
Section: Discussionmentioning
confidence: 52%
“…Indeed, we have recently shown that MPR is associated with aerobic exercise capacity in asymptomatic adults with T2D, independent of age, sex, ethnicity, smoking status, glycaemia and diastolic function. 5 This suggests a central role for microvascular dysfunction in SBHF in people with T2D.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially significant given the vast majority of people with T2D develop heart failure with preserved ejection (HFpEF), a condition that has no proven effective treatments. 4 We have recently demonstrated that subclinical concentric LV remodelling, arterial stiffening, abnormalities in diastolic and systolic function, and reduced myocardial perfusion are present in T2D, 5 , 6 and these features are increasingly recognised as pathognomic features of SBHF and precursors to the onset of clinical heart failure. 4 , 5 The clinical factors contributing to early cardiovascular dysfunction in people with T2D, however, are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronary microvascular dysfunction is associated with a higher BMI, is linked to increased microvascular resistance and provides independent prognostic information for cardiovascular risk in obese patients 34,35 . Asymptomatic diabetic patients undergoing cardiac MRI have also been shown to have decreased myocardial blood flow from microvascular dysfunction, a finding that was linked to reduced peak VO 2 36 . Thus, inducible myocardial dysfunction may be the result of endothelial dysfunction and coronary microvascular dysfunction.…”
Section: Discussionmentioning
confidence: 99%